Actividad espacio-temporal de Polietes meridionalis Peris & Llórente , 1963 ( Díptera : Muscidae ) en un ecosistema de encinar * (Boletín de Sanidad Vegetal Plagas, 1995)
Some aspects of the biology of Polietes meridionalis Peris & Llórente 63 have been analysed in a holm-oak ecosystem (dehesa) located in the Tberian Mediterranean área. The specimens were caught with pit-fall traps baited with cattle dung, placed according to habitat gradient. They were collected at dífferent hourly periods to fix a distribution model in space and time and its variation during the year.